Knowledge Structure and the Estimation of Conditional Probabilities in Audit Planning - Nelson, Mark W.; Libby, Robert; Bonner, Sarah E. (The Accounting Review, 1995)
[Experienced auditors tend to structure their knowledge of financial statement errors with audit objective as the primary organizing dimension and transaction cycle as secondary. Yet, many audit tasks are structured in the opposite manner, requiring auditors to assess whether objectives are met for each transaction cycle. Our paper reports the results of an experiment which indicates that this mismatch between knowledge structure and task structure may hinder auditors' ability to draw on previous experiences when making conditional probability judgments and when allocating audit hours to various objectives within cycles. These results suggest one instance where knowledge structures that are often functional may have adverse effects when they do not match the task structure to which they are applied.]